Membrane bioreactor for sewage treatment - Nik Shamim Uzaini , Nik Zulkiffli (2012)
Sewage is the highest contributor to the world's water pollution which contributes 60% of the pollution which is kindly straightly comes from the municipal and domestic/residential. Sewage water treatment is a must, when environmental issues are an increasing concern. Submerged membrane bioreactor (MBR) is a technology which is able to fulfill those specific purposes. The Membrane Bioreactor (MBR) process is an emerging advanced wastewater treatment technology that has been successfully applied. The combination of membrane separation with a suspended growth bioreactor is now widely used for waste treatment. The raw sample has shown that it fulfilled the characteristic of sewage where the value of Chemical Oxygen Demand, Suspended Solids and Biochemical Oxygen Demand are higher than what have being comply in Environmental Quality Act 1979 Maximum Effluent Parameter Limits Standard A and B. Pink and blue colours developed since nitrate and phosphorus are present in the sewage. In this project, Chemical Oxygen Demand and Suspended Solids have been chose to be the monitor parameter where HRT and microfiltration affects the performance of the sewage quality. Even the result do not comply the standard, somehow the sewage quality improved all along the experimental run. At 4 hours HRT, COD resulted 135mg/1 at I bar while SS resulted lOmg/l at also I bar pressure. It shows that at lowest HRT and pressure, the treatment is getting better. The treatment is through microfiltration which is typically required low pressures (0.2 to 0.5 bar) to obtain the selective separation and HRT for MBR's are typically 4 to 20 hours since on most domestic wastes, this is enough time to allow for the oxidation of organic material which explain why 1-flU' 24 hours resulted COD and SS values at 279mg/l and 31mg/I at 3 bar pressures. This shows that membrane bioreactor process is capable in treating sewage wastewater at low HRT and pressure.